How posture influences venous blood flow in the lower limbs: results of a study using photoplethysmography. Issue 2 (3rd April 2017) - Łastowiecka-Moras, Elżbieta
Abstract : Prolonged standing or sitting is one of the factors for chronic venous insufficiency. The aim of the study was to determine the impact of static load of the lower limbs on the functioning of the venous system. The study included 10 healthy young participants, with no peripheral venous disease. All participants took part in examinations in two variants: variant 1, sitting for 20 min with the lower limbs bent in the knee joints at 90°; variant 2, standing for 20 min with no additional load. Before and after each test, the venous refilling time (VRT) was determined using photoplethysmography. Statistical analysis demonstrated that the VRT was significantly shortened only after application of variant 2. Furthermore, even variants with small loads applied to healthy young participants can induce in them effects on the parameters describing the peripheral circulation.